2019
DOI: 10.1053/j.gastro.2019.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive and Gut-Reparative Functions of Human Type 1 T Regulatory Cells

Abstract: BASIC AND TRANSLATIONAL AT might be developed as a cell-based therapy for intestinal inflammatory disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 43 publications
1
56
0
Order By: Relevance
“…However, a previous study reported an increased percentage of Tregs as part of CD diagnosis, as well as during the active phase of the disease (Smids et al, 2018). Tregs generally suppress IL-1B production and inhibit effector T cell proliferation, whereas some studies reported that these function are impaired in CD (Maloy and Powrie, 2011;Cook et al, 2019). This suggests that Treg status in CD remains controversial and might depend on inflammatory stage.…”
Section: Discussionmentioning
confidence: 98%
“…However, a previous study reported an increased percentage of Tregs as part of CD diagnosis, as well as during the active phase of the disease (Smids et al, 2018). Tregs generally suppress IL-1B production and inhibit effector T cell proliferation, whereas some studies reported that these function are impaired in CD (Maloy and Powrie, 2011;Cook et al, 2019). This suggests that Treg status in CD remains controversial and might depend on inflammatory stage.…”
Section: Discussionmentioning
confidence: 98%
“…In peripheral blood of CD and UC patients circulating Tr1 frequencies may not differ from those of healthy individuals. Moreover, when isolated the cells have a similar phenotype and cytokine profile [248]. However, human intestinal IFN-γ-producing Tr1 cells co-expressing CCR5 and PD1 were found to down-regulate IL-10 in patients with IBD [249].…”
Section: The Role Of Tr1 Cells In Ibdmentioning
confidence: 93%
“…In a Phase I/II clinical trial with refractory CD, infusion of ovalbumin-specific Tr1 cell clones was tolerated and showed dose-dependent efficacy in patients suffering from severe disease suggesting the approach may have potential [255,256]. In particular, as functionally suppressive Tr1 cells can be isolated from the peripheral blood of IBD patients and expanded in vitro autologous Tr1 cells transfer could be a therapeutic option [248].…”
Section: Does Adoptive Transfer Of Tr1 Cells Attenuate Disease?mentioning
confidence: 99%
“…In a similar manner, hybrid culture organoids with immune cells has allowed for ex vivo modelling of immuno-epithelial interactions, which include the cross-talk between leukocytes and organoids [102][103][104][105] , cytotoxicity of chimeric antigen-engineered lymphocytes 106 and tumour education of circulating T cells by co-culture with autologous tumour organoids 107 (Fig. 5b).…”
Section: Organoid Reverse Engineering For Genetic Disease Modellingmentioning
confidence: 99%